A Test Scheme Design for High Speed Active Cabin Separation. (October 2019) - Feng, Wei; Li, Changxun; Meng, Fanwei; Chen, Qiwei; Yi, Wangmin; Zheng, Shengyu; Wang, Linzheng; Wang, Chenxing; Zhang, Lili
Abstract: In Mars explorations, the EDL (Entry, Descent and Landing) process is autonomously controlled, called "black 7minutes". In order to verify the EDL process of the Mars probe cabin (the heatshield facing the Mars surface and the aeroshell back to the surface of Mars) high speed separated, this paper proposes an active motor pull separation scheme and controlling method of axial force, normal force and torque multi-coupling, solves the technological problem of the force applied, followed and safe recycling cabin in short time and distance, establishes a test system and completed the separation test of the heatshield and the aeroshell by real product. The results show that the test success criteria are met and the test scheme is successful. This method and experimental system can be used not only in the separation experiment of Mars probe, but also in the separation or servo simulation of other detectors or general mechanisms, can be widely used or used for reference. This paper explains the general scheme and key technology, followed by other papers on ADAMS Simulation, influence on air-resistance and so on.